Bioinspired Multifunctional Self-Sensing Actuated Gradient Hydrogel for Soft-Hard Robot Remote Interaction - He Liu; Haoxiang Chu; Hailiang Yuan; Deliang Li; Weisi Deng; Zhiwei Fu; Ruonan Liu; Yiying Liu; Yixuan Han; Yanpeng Wang; Yue Zhao; Xiaoyu Cui; et al. (Nano-Micro Letters, 2024)
Highlights The bioinspired self-sensing actuated gradient hydrogel was developed by a wettability-based method via precipitation of MoO2 nanosheets. Self-sensing actuated gradient hydrogel combined ultrafast thermo-responsive actuation (21° s–1), exceptional photothermal efficiency (3.7 °C s–1) and high sensing properties (GF = 3.94). The first self-sensing remote interaction system based on gradient hydrogel actuators and robotic hands was constructed.